The Application Of Maja Labo Dahu Cultural Values In Overcoming Conflicts Between Communities In Parado Sub-District, Bima District, West Nusa Tenggara - Jumrati; Arifuddin; Kamaluddin Tajibu (TASAMUH, 2024)
This research discusses "The Application of Maja Labo Dahu Values in Conflict Resolution in Parado Subdistrict, Bima Regency, West Nusa Tenggara," with the following research questions: 1) What forms of conflict commonly occur in Parado Subdistrict, Bima Regency? 2) How are the cultural values of Maja Labo Dahu applied to resolve conflicts among the community in Parado Subdistrict, Bima Regency? This study is qualitative, employing a sociological approach. Data sources are obtained from both primary and secondary data. Data collection methods include direct interviews with informants, supported by other data from observation and documentation. The data analysis involves three stages: data reduction, data presentation (display), and conclusion drawing. The research findings indicate that conflict in the Parado community includes brawls between individuals and group fights. These conflicts, often sparked by the actions of young people, are primarily triggered by the tradition of joget (dance) parties and alcohol consumption. The application of Maja Labo Dahu values, such as patience in actions, the principle of family and deliberation, and mutual cooperation, is still seen as crucial for fostering harmony within the community of Parado Subdistrict. The implications of this study suggest the need for continued application of Maja Labo Dahu values. Additionally, there should be enhanced communication and exemplary leadership from local leaders who must focus more on improving harmony and solidarity. All parties must agree on abolishing the culture of dance parties and imposing strict regulations, along with penalties, on the distribution, provision, and sale of alcoholic beverages, whether from inside or outside the community. In particular, youth require serious attention, as proactive steps must be taken to safeguard future generations.